Gramsci contested interpretations, debates, and polemics, 1922-2012 - Liguori, Guido (Brill, 2022)
"Gramsci Contested is a map with which one can orient oneself in the many readings, debates and controversies that surround Gramsci's work. From the judgements of his contemporaries to the peak of his fame and the apparent decline of his star in the 1990s, we are guided through the entire history of Gramci interpretation, including the great majority of the philological, political and historical readings in which his writings have been taken up and put to work. Liguori argues that a knowledge of Gramsci is essential to understanding where the Italian left comes from, as well as to critical thought and Marxism in the world today"--
Translated from the Italian
Keywords: Gramsci, Antonio / 1891-1937 / Influence; Communism / Italy / History; Socialism / Italy / History; Gramsci, Antonio / 1891-1937; Communism; Influence (Literary, artistic, etc.); Socialism; Italy; History